Liquorice (glycyrrhiza glabra) hydroethanolic extracts effectively alleviate thioacetamide -induced hepatotoxicity and hematotoxicity in experimental rats through their antioxidant nature - Behairy, Alaa; Elkomy, Ashraf; Elsayed, Faten (International Journal of Pharmacology and Toxicology, 2020)
Background: Liquorice (Glycyrrhiza glabra) is a high valued plant and used in a lot of countries around the world. The liquorice (LQ) has a remarkable medicinal, nutritional and socio-economic value. Therefore this study was designed to clarify the protective effect of liquorice hydroethanolic extract against Thioacetamide (TAA) induced hepatotoxicity and hematotoxicity in rats.Materials and Methods: Seventy white Albino male rats were used in this study and after acclimatization rats were subjected to different treatments blood and tissue samples were collected after day 30 post administration, biochemical, antioxidant, hematological and histopathological examinations were utilized to investigate hepatoprotective activity of liquorice hydroethanolic extract.Results: TAA significant (P
Keywords: Hematotoxicity; Hepatotoxicity; Liquorice Extract; Rats; Thioacetamide.